Synthetic Reality and Blind Flight: The Operationalization of Perception - Franz, Nina; Ladewig, Rebekka (Politik, 2017)
In our contribution we trace the emergence of human perception as an actual object of design and engineering in the early history of aviation through the postwar rise of human factors studies, and into military research and its respective industries today. In this survey, (perceptual) engineering and high-technology weapons such as remote- controlled or (partially) automated drones blend into a military policy that distances human operators from the ‘theater of war.’ As we argue, this new form of warfare with its visual technologies (‘Synthetic Vision Systems’) and mental ecologies (Situational Awareness) is aligned with a ‘logic of simulation,’ as discusses by Jacques Rancière in his political theory of in/visibility.